Effects of Tanreqing injection against ventilator-associated pneumonia: a meta-analysis and systematic review of clinical studies - Li, Pochen; Wu, Yang; Ge, Danxia; Xu, Ruyi; Zhang, Qianping; Li, Yujiao; Zhang, Lingyao; Peng, HsuanChieh; Yu, Fangyu (Frontiers in Pharmacology, 2025)
ObjectiveVentilator-associated pneumonia (VAP) frequently results in difficulties with weaning, high mortality rates, and is often caused by drug-resistant pathogens, emphasizing the critical importance of effective treatment. The efficacy and safety of Tanreqing injection (TRQI) in the treatment of VAP patients have been demonstrated, but further validation is required. The objective of this study is to synthesize the findings of clinical research on TRQI for the treatment of VAP, thereby providing clinical evidence for its effectiveness and importance.MethodsA comprehensive search of eight databases was conducted, covering all records up to 30 August 2024. The data were extracted, quality-assessed, and analyzed rigorously. The methodological quality of the included studies was evaluated using the RoB-2 tool. The statistical analyses were conducted using RevMan 5.4 software, with either a fixed-effect or random-effect model employed as appropriate. The evidence quality of the included literature was evaluated using Grade pro 3.6.1 software.ResultsA total of 20 clinical studies, comprising a total of 1,446 patients, were included in the review. The meta-analysis of these studies demonstrated that TRQI significantly improved inflammatory markers (CRP, PCT, WBC) (P < 0.00001) and reduced the duration of antibiotic use (P < 0.00001). Furthermore, the intervention resulted in a shorter duration of ventilator usage (P < 0.0001), an increased initial weaning success rate (P = 0.001), and a reduction in the length of stay in the intensive care unit (ICU) (P < 0.00001). Furthermore, the TRQI demonstrated superior performance compared to the control group in CPIS (Clinical Pulmonary Infection Score) assessments (P < 0.00001). Meanwhile, the quality of evidence for CRP, PCT, Duration of Antibiotic Use, Duration of Ventilator Use, and Length of ICU Stay is Moderate.ConclusionThis study provides further evidence-based support for the clinical application of TRQI in the treatment of VAP. Additionally, it summarizes previous clinical research through a literature quality assessment, offering insights and recommendations for the design and implementation of future research protocols. The findings indicate that TRQI can improve inflammatory markers and pulmonary infection scores in VAP patients, reduce ventilator dependence, and shorten antibiotic use duration. Moreover, it has a low overall incidence of adverse reactions, demonstrating good efficacy and safety as an adjuvant therapy for VAP. However, some of the included clinical studies had limitations such as small sample sizes, lack of sample size calculations. Therefore, future study designs should be more rigorous to enhance the reliability of findings.Systematic Review Registration:https://inplasy.com/inplasy-2025-2-0008/.